Street Children: Risks and Implications . A Field Study in Anbar Governorate - Assist. Prof. Dr. Noori Saadoon Abdullah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Children represent the important element on which the burden of development falls, and therefore it is imperative that children receive what is worthy of them in terms of material and moral care, through which they can meet their needs during the growth period, in order to become healthy and sound. The interest in childhood issues occupies the attention of the developed and developing world alike, whether the child is the future, and global concern has crystallized to the issuance of the Declaration of the Rights of the Child in 1959 AD and the Convention on the Rights of the Child in 1989 AD. Despite all this interest in childhood issues, there are many children who still suffer from living in difficult circumstances and are exposed to many working conditions within the community that push them to beggary and some deviations, as a result of the failure to satisfy their basic needs and the low level of material and moral care that they receive, whether from Family and society, as there are many children who suffer from deprivation of parental care and are under psychological and social pressures that make them vulnerable to falling into the circle of danger. The researcher will try to identify the most important challenges and risks that result from mishandling of children, what are the conditions that beggary children suffer, and try to reach results and conclusions that will limit these cases, and the research has reached goals, the most important of which are: . 1.Identify the most important challenges resulting from the problem of street children and their repercussions on society. Knowing the dangers that street children are exposed to. Identify the most important repercussions left by the displacement crisis on street children. This study is considered from field descriptive studies and the researcher uses the method of social survey, field interviews and simple observation as basic tools for data collection. The threshold for research has reached (120) cases of street children in the various districts of Anbar Governorate.